Development of elderly reminder mobile application using mental model - Baharum A.; Ismail R.; Saad N.; Daruis D.D.I.; Noh N.A.M.; Noor N.A.M. (Association for Computing Machinery, 2023)
Artificial intelligence; Cognitive systems; Mobile computing; Virtual reality; Elderly; Elderly users; Mental model; Mobile applications; Navigational design; Quality of life; Quantitative method; User interface designs; User interfaces